The Effect of Using the Duolingo Application on Elementary School Students' Mastery of English Vocabulary - Suhendra, Nabila Nurhaliza; Antik Sari, Nadia Tiara; Wahyudin, D (Educational Studies and Research Journal, 2024)
Language, particularly English, which is an international language in Indonesia, is used to communicate in a variety of circumstances. However, many people still do not recognize that teaching vocabulary to children is critical since vocabulary impacts a person's capacity to string words to communicate, therefore it is essential to master when studying English. This is demonstrated by the low mastery of the English language among fourth-grade pupils at SDN Purwamekar Purwakarta District, Purwakarta Regency. Previous academics have identified learning media as a message technology that can be used for educational reasons. Previous academics have identified learning media as a message technology that can be used for educational reasons. The use of the Duolingo app is one of the technology-based English learning approaches. The research approach employed was pre-experimental, with a one-group pretest-posttest design and a simple random sample technique. Its goal is to assess fourth-grade students' comprehension of English vocabulary before and after treatment with the Duolingo application, as well as to determine the effect. This study included a total of 30 students. The findings revealed that (1) the average value of elementary school pupils' descriptive tests for vocabulary knowledge in English before using the Duolingo application was 42.67. (2) After two sessions of treatment with the Duolingo application, the average score of primary school pupils' English vocabulary knowledge climbed to 80.33 from the descriptive test average. (3) The findings of the basic linear regression test suggest that using the Duolingo app improves elementary school students' comprehension of English vocabulary by 24.9%. It may be concluded that variable x, namely the usage of the Duolingo application, influences variable y, namely the mastery of English vocabulary of grade IV primary school pupils, allowing kids to master vocabulary.